Synthesis of baseline GHG emission data and estimation methods in aquatic food systems in Vietnam - Le, Quyen; Hoang, Cuong; Tran, Nhuong (WorldFish, 2023)
Drawing data and information from desk-based reviews, key informant interviews, and group discussions with relevant stakeholders in Vietnam, this working paper compiled and analyzed emission baseline data of greenhouse gas (GHG) from Vietnamese aquatic food systems, focusing on key aquaculture systems of fish, crustaceans, mollusks, and seaweed, together with capture fisheries and post-harvesting and processing of aquatic foods.